Integrating portfolio and mentorship in competency-based medical education: a Middle East experience - Mariam Shadan; Rania H. Shalaby; Arina Ziganshina; Samar Ahmed (BMC Medical Education)
Abstract Background Within the context of competency-based medical education, portfolios and mentorship emerge as complementary interventions, each offering distinct perspectives and benefits. Together, these elements synergistically contribute to a holistic and effective approach to medical education, encompassing both the academic and personal development imperatives of students. However, this integration comes with several implementation challenges that must be anticipated and promptly addressed. After reviewing the literature related to the enabling factors and barriers to the successful integration of mentoring and portfolio assessment, Dubai Medical College for Girls (DMCG) developed a strategy to minimize all known limitations of this approach. The article provides solutions to compensate for the reported gaps in the system's performance. Practical tips are provided for the effective implementation of an integrated portfolio and mentorship approach to maximize educational outcomes. The article details original responses to common challenges in this process, such as standardizing portfolio content, optimizing time investment in mentorship, and maintaining the value of portfolios in an assessment-centric educational framework.  Conclusion DMCG experience and literature data suggest that the implementation of the integrated approach to mentorship and portfolio assessment can be successful if during operationalization institution administrators consider several important factors including participant training and support, timely introduction of the system, standardization of portfolio content and agenda of the mentor–mentee meetings, convenience for system users, wise scheduling, and emphasizing reflective component.